Screening for in vitro amoebicidal activity of plant essential oils against Acanthamoeba sp. - Wannasan, Anchalee; Sanguan, Suthida; Junkum, Anuluck; Jitpakdi, Atchariya; Riyong, Doungrat; Champakaew, Danita; Pitasawat, Benjawan (Biomedical Sciences and Clinical Medicine, 2018)
Objective To screen for in vitro amoebicidal activity of essential oils extracted from 10 plant species from three botanical families against Acanthamoeba sp. Methods Essential oils were extracted from dry material of 10 plant species using steam distillation; the percentage yields and physical characteristics of the derived essential oils were recorded. The cyst and trophozoite stages of Acanthamoeba sp. were harvested separately from monoxenic agar and axenic peptone yeast glucose (PYG) cultures, respectively. Amoebicidal activities of each essential oil were determined in vitro at a concentration of 50 mg/mL. After 24 h of incubation, morphological changes, cell viability, and percentage mortality of amoebae were investigated using a light microscope. Results Essential oils were successfully extracted from all ten plant species with average yields on a dry weight basis ranging from 0.3 to 6.7% (v/w). Five out of the ten essential oils tested, including the oils of Piper retrofractum Vahl., Piper nigrum Linn., Citrus hystrix DC., Curcuma longa Linn., and Kaempferia pandurata Roxb., effectively eradicated Acanthamoeba trophozoites, with mortality up to 100%. Furthermore, both P. retrofractum and C. hystrix oils also exerted cysticidal activity against Acanthamoeba sp., with 3.35% and 43.62% mortality, respectively. Conclusions This is the first report on the amoebicidal activities of these essential oils, of which the most effective were the P. retrofractum and C. hystrix oils which affected both the trophozoite and the cyst stages of Acanthamoeba. The results of this study provide basic knowledge for future studies of the amoebicidal potential of these plant essential oils which could potentially be developed and applied for the treatment of acanthamoebiasis for which no effective drug is currently available